Edukasi Dan Sosialisasi Diabetes Melitus Di Kelurahan Muara Dua Kota Prabumulih - Edwid, Suharti; Wahyuni, Sri; Ardiansyah, Rebi; Susila, Nisa; Yani, Rahma; Rosanti, Yulli; Aprianthy, Ida Rizkhy; Sudiyanto, Sudiyanto; Rohani, Tuti; Azissah, Danur (Jurnal Dehasen Mengabdi, 2025)
The prevalence of diabetes is increasing in line with lifestyle changes such as lack of exercise and frequent consumption of unhealthy foods such as fast food, which is happening in many countries today. For now, diabetes can affect anyone, including children, teenagers, adults and the elderly. This socialization and education activity aims to help increase the number of people with diabetes mellitus in Muara Dua Village.Diabetes mellitus is a disease that is always included in the top 10 most diseases based on the number of visits at the Delinom Health Center in Prabumulih City. The methods used in socialization and education are the elaboration of diabetes mellitus such as risk factors, complications, insulin therapy, diabetes mellitus diet and diabetic melitus foot care. In addition to the explanation, there was also a leaflet that was distributed to all the elderly who attended. Thus, it is hoped that public knowledge about Diabetes Mellitus will be greater so that it will be able to reduce the rate of increase in Diabetes Mellitus sufferers.